Pengaruh Likuiditas dan Struktur Modal Terhadap Profitabilitas Pada Perusahaan Manufaktur Subsektor Semen yang Terdaftar di Bursa Efek Indonesia - Rahmawati, Eli; Ruma, Zainal; Nurman; Ichwan Musa, Muhammad; Budiyanti, Hety (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2023)
This study aims to test the effect of capital (debt to equity ratio) on profitability on the cement subsektor company listed on the Bursa Efek Indonesia (2013-2022) with the total number of samples of 40 samples. The method used in this research is quantitative method with hypothesis test using SPSS version 27 version. The results of the research show that the current ratio variabel has a positive and insignificant effect on return on equity, as evidenced by the calculated t value < t tabel, namely 0,572 < 1,69092 with a significance value of 0,571 > 0,05 and the debt to equity ratio variabel has a negative and significant effect on returns. on equity is proven by the t value > t tabel, namely 2,384 > 1,69092, the t value is negative and the significance value is 0,023 < 0,05. Simultaneously the current ratio and debt to equity ratio influence return on equity, this is proven by the calculated F value of 4,278 > F tabel 3,27 and the obtained significance value of 0,022 < 0,05.